1999
DOI: 10.1007/s004670050614
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of amlodipine in pediatric patients with hypertension

Abstract: We designed a study to determine the efficacy and safety of amlodipine given once daily in the pediatric population. Twenty-one patients (mean age 13.1 years) with either essential (n=160) or renal (n=5) hypertension, and newly diagnosed (n=15) or poorly controlled or intolerant on existing antihypertensive therapy (n=6), were included. Patients received amlodipine once daily at a starting mean dose of 0.07+/-0.04 mg/kg per day. The total daily dose of amlodipine was increased 25%-50% every 5-7 days if the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 31 publications
2
33
1
Order By: Relevance
“…11,19 The side effects noted in our paediatric patients given amlodipine are similar to those reported in adults and children treated with amlodipine or other dihydropyridines. [1][2][3][4]18,[20][21][22][23] These vasodilators lead in 10 to 20% of patients to one or more of the following: headache, dizziness or lightheadedness, flushing, and peripheral oedema. The peripheral oedema is related to redistribution of fluid from the vascular space into the interstitium, possibly induced by vasodilatation which allows more of the arterial pressure to be transmitted to the capillary circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,19 The side effects noted in our paediatric patients given amlodipine are similar to those reported in adults and children treated with amlodipine or other dihydropyridines. [1][2][3][4]18,[20][21][22][23] These vasodilators lead in 10 to 20% of patients to one or more of the following: headache, dizziness or lightheadedness, flushing, and peripheral oedema. The peripheral oedema is related to redistribution of fluid from the vascular space into the interstitium, possibly induced by vasodilatation which allows more of the arterial pressure to be transmitted to the capillary circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally dose adjustment is superfluous in renal impairment. [1][2][3][4]16,17 Paediatric use of amlodipine has previously been reported, 12,18,[20][21][22][23] but previous reports have been limited by small patient numbers 12,[20][21][22][23] and rather heterogenous patient populations, that included both in-and outpatients 18,20 or both renal and non renal hypertension. 12,18,20,21 In conclusion the results of the present experience in paediatric outpatients with chronic kidney diseases support the view that amlodipine is an effective and rather well tolerated antihypertensive drug when given once a day in a dosage of 7 to 10 mg/m 2 body surface area and suggest that it has obvious advantages over other dihydropyridines.…”
Section: Discussionmentioning
confidence: 99%
“…123 In a separate trial of 21 adolescents, ABPM was used to demonstrate the efficacy of amlodipine, a calcium channel blocker, as an effective once-daily antihypertensive agent. 124 Despite the paucity of data on the use of ABPM in monitoring hypertensive treatment in children, a recent survey of 438 North American pediatric nephrologists found that the majority favor use of ABPM for this purpose. 125 The increasing clinical use of ABPM is likely to spur further interest in the use of ABPM in pediatric antihypertensive trials.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Amlodipine studies 14 showed larger dose requirement per kilogram for patients younger than 13 years vs an older group ( Table 2). The only oral hypoglycemic drug approved for children with type 2 diabetes was metformin.…”
Section: Examples Of Our Workmentioning
confidence: 99%